Beyond consent: improving data protection through consumer protection law - Michiel Rhoen (Internet Policy Review, 2016)
As a result of datafication (the generation and acquisition of personal data from automated processes), consumers' activities generate large data streams. Analysis of these streams reduces privacy and shifts power towards data controllers. Consumers often contractually agree to this analysis of their data, but their autonomy can be questioned: the agreements often contain non-negotiable terms unilaterally drafted by data controllers. Consumer protection law can alleviate this power shift towards data controllers, but only if EU member states increase their enforcement efforts.
Keywords: 300; Data protection; Consumer protection; Privacy; Big data